FK506 Resistance of Saccharomyces cerevisiae Pdr5 and Candida albicans Cdr1 Involves Mutations in the Transmembrane Domains and Extracellular Loops - Tanabe, Koichi (Antimicrob Agents Chemother, 2018)
The 23-membered-ring macrolide tacrolimus, a commonly used immunosuppressant, also known as FK506, is a broad-spectrum inhibitor and an efflux pump substrate of pleiotropic drug resistance (PDR) ATP-binding cassette (ABC) transporters. Little, however, is known about the molecular mechanism by which FK506 inhibits PDR transporter drug efflux. Thus, to obtain further insights we searched for FK506-resistant mutants of Saccharomyces cerevisiae cells overexpressing either the endogenous multidrug efflux pump Pdr5 or its Candida albicans orthologue, Cdr1. A simple but powerful screen gave 69 FK506-resistant mutants with, between them, 72 mutations in either Pdr5 or Cdr1. Twenty mutations were in just three Pdr5/Cdr1 equivalent amino acid positions, T550/T540 and T552/S542 of extracellular loop 1 (EL1) and A723/A713 of EL3. Sixty of the 72 mutations were either in the ELs or the extracellular halves of individual transmembrane spans (TMSs), while 11 mutations were found near the center of individual TMSs, mostly in predicted TMS-TMS contact points, and only two mutations were in the cytosolic nucleotide-binding domains of Pdr5. We propose that FK506 inhibits Pdr5 and Cdr1 drug efflux by slowing transporter opening and/or substrate release, and that FK506 resistance of Pdr5/Cdr1 drug efflux is achieved by modifying critical intramolecular contact points that, when mutated, enable the cotransport of FK506 with other pump substrates. This may also explain why the 35 Cdr1 mutations that caused FK506 insensitivity of fluconazole efflux differed from the 13 Cdr1 mutations that caused FK506 insensitivity of cycloheximide efflux.